Flipped Learning in Higher Education: Accelerated Learning, Students' Perception of the Learning Process and Self-esteem - García Gómez, Antonio (2019)
Both educators and psychologists have called attention to a need to spark innovation in the classroom in general and in the university classroom in particular. The use of ICT and the implementation of new approaches to teaching that allow, on the one hand, teachers to cater for diversity and, on the other hand, students to take the reins of the learning process havebecome the building block of innovation at university level. The present study describes the implementation of a flipped classroom approach with university students that are studying content through English as Foreign Language. Using a control group (45 students) and anexperimental group (44 students), the results show that the implementation of a flipped classroom approach seems to accelerate students’ learning. Apart from the academic results, the study also gives evidence of the positive impact on students’ self-esteem.